A Comparative Clinical Study Of Implants In The Posterior Maxilla: Methods Of Sinus Floor Augmentation Versus Standard Implantation - F. Atamni; V. Topalo (Romanian Society of Oral Rehabilitation, 2010)
The purpose of this study was to evaluate the secondary stability of implants placed in the posterior Maxilla according to different surgical techniques of sinus floor augmentation versus standard implantation. 128 patients had been treated between the years 2005 to 2009 with SLA screw implants in the posterior maxilla. 3 surgical techniques have been performed depending on the residual bone height: lateral approach sinus floor elevation with graft material (Bio-Oss) in 30 patients with 88 simultaneous placed implants, flapless transalveolar sinus floor elevation without graft material in 50 patients with 66 placed implants, 79 Implants in 48 patients with standard implantation(control group). Periotest values (PV) of each implant in all groups were analyzed. No statistically differences were found between the groups. Clinical evaluations of the results showed stable implants according to PV.